Malnutrition and Its Determinants: A Population Based Study among Children of 5-59 Months at District Swat, Pakistan - Ullah, Naeem; Humayun, Muhammad; Ishtiaq, Muhammad; Ullah, Imran; Khan, Faiza Humayun (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Background: Globally, malnutrition is one of the major public health problems and affects all ages. This cross-sectional study was conducted to estimate the frequency and potential determinants of malnutrition among the children of age 5-59 months at District Swat, Pakistan. Methodology: A cross-sectional study was conducted among children of age 5-59 months at Swat, Pakistan, from October, 2018 to April, 2019. After ethical approval, 200 children were assessed to estimate the frequency of malnutrition and the potential determinants related to malnutrition. A structured questionnaire was used for data collection. Strict inclusion and exclusion criterion was followed and individuals on the basis of BMI were categorized into normal, under-nutrition and over-nutrition classes. The data was analyzed by SPSS version 19.0. Finally, results were presented in tabular form. Results: The prevalence of malnutrition was 48%. The prevalence of under nutrition was 40.5% and over nutrition 11.5%. Moreover, 43% had mild; 21% had moderate and 17% had severe malnutrition. Approximately, 49% had age above 24 months; 46.5% were illiterate; 30% had monthly income > PKR40000, 79.5% were breastfed; 14.5% were bottle-fed; 39.5% used pre-lacteals; 59.5% had history of infections; and 52% started weaning at correct time. Conclusions: The prevalence of malnutrition was high (48%) among 5-59 months children and showed relationship with monthly income, mothers literacy, family size, and BMI of mothers and children. Moreover, malnutrition also revealed strong relationship with breast feeding, weaning, and acute and chronic infections. Thus, effective mother and child health-care (MCH) services along with growth and monitoring measures were needed to improve the nutritional status of the community. Key words: Frequency, Malnutrition, Underweight, Illiteracy, Breast Feeding, Weaning, Swat